Spatial and Temporal Analysis of Thermal Comfort Before the Pandemic, Lockdown, and the Covid-19 Pandemic Transition Period in Yogyakarta City, Indonesia Using Modified Temperature-Humidity Index - Hadibasyir, Hamim Zaky; Diharjo, Dwi Apriyani; Putri, Dewi Kurnia; Sari, Dewi Novita; Fikriyah, Vidya Nahdhiyatul; Firdaus, Nada Salsabila (Amcolabora, 2024)
Yogyakarta as a city of education and a tourism city has the potential to experience a very significant change in the concentration of anthropogenic activity between before the pandemic and when the lockdown policy was implemented. Also, during the pandemic transition period, it allows for changes in fluctuating thermal comfort. This study aims to analyse thermal comfort before the pandemic, lockdown, and transition of the Covid-19 pandemic in Yogyakarta City. This study utilised Landsat 8 images before the pandemic, lockdown, and the transition to the Covid-19 pandemic. Next, the land surface temperature (LST) and Normalized Difference Moisture Index (NDMI) were extracted. The LST and NDMI values are then processed to obtain thermal comfort in the form of the Modified Temperature-Humidity Index (MTHI). There was no clear pattern regarding MTHI (as a proxy of thermal comfort) before the pandemic, during the lockdown, and during the Covid 19 pandemic transition in the City of Yogyakarta. This study confirmed that there is a need of a better spectral index that reflects thermal comfort condition of a region.